Danza folclórica contemporánea: experiencias de resignificación de la práctica escénica del folclor desde la investigación-creación - Castro Mozo, Jair Jaime (Universidad Antonio Nariño, 2022)
The present work shows the results of the research project "Contemporary folk dance: experiences of resignification of the scenic practice of folklore from research-creation process" which aims to reveal the motivations, conceptions, and methodologies implemented by Jaime Jair Castro Mozo in the conceptualization and framework enunciated as "contemporary folk dance" observable in the Danzamarios company’s creative processes from 2016 to 2021 in Santa Marta, Colombia